Mortality And Economic Impact of African Swine Fever (ASF) Outbreak on Pigs in Luwu Timur Regency - Suartana, Dewa Putu; Suryanto; Arzam, Taruna Shafa (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
Understanding the impact of ASF comprehensively is a crucial step in efforts to control and prevent future outbreaks. Therefore, an in-depth study is needed on the "Mortality and direct economic impact of African Swine Fever (ASF) outbreak" on pigs in East Tomoni District. This study was conducted in East Tomoni District, East Luwu Regency, South Sulawesi Province. Given the population of more than 1001 people, 5% of the population (1,085 farmers) were used as research samples. This study uses a comprehensive approach to evaluate economic losses due to ASF in the Tomoni Timur District. By considering three main aspects, namely pig mortality, direct losses to pig farms, and government losses. The analysis results show that the mortality rate of pigs due to ASF in the ASF outbreak in Tomoni Timur District caused pig mortality of up to 99.46%, having a major impact on the livestock population and the local economy. The economic loss per household reached IDR 55 million, reflecting a significant impact on farmers. The government also bears the cost of handling more than IDR 1 billion, but the main burden remains on farmers. The high number of losses shows the importance of appropriate interventions to prevent similar impacts in the future. More effective prevention strategies need to be designed to reduce the risk of recurrence. The mortality rate of pigs in East Tomoni District due to ASF is very high.